PENDAMPINGAN BELAJAR MATEMATIKA SISWA KELAS VIII C MTs S MODERN ARAFAH MATERI PERSAMAAN GARIS MELALUI DUA TITIK - Norhaslina, Norhaslina; Hesti, Nadiya; Andina, Andina; Putra, Aan (ABJIS: Al-Bahjah Journal of Islamic Community Service, 2024)
The aim of this assistance is to improve understanding and skills for students who have difficulty learning mathematics, especially in the material "Equations of Lines Through Two Points". The implementation of this community service research follows the activities of carrying out action research which consists of preparation or planning, implementation or evaluation. Mentoring was carried out at MTs S Modern Arafah for class VIII C students regarding the equation of a line through two points. Mentoring is carried out by 3 mentors, each mentor accompanies 2 students who are experiencing difficulties in learning mathematics. The results of mentoring show that students feel helped and can have a positive impact. This can be seen from the enthusiasm of students who always ask about the material and steps to solve problems that students don't understand so that it can foster students' enthusiasm for learning in mathematics learning.